Endemic hepatitis b and c virus infection in a brazilian eastern amazon region - El Khouri,Marcelo (2010)
CONTEXT: Hepatitis B and hepatitis C infection has been an important cause of morbidity and mortality around the world. However there are few investigations regarding the prevalence and possible risk factors for these diseases in Brazil, particularly in Amazon region, where there are some endemic focus. OBJECTIVES: To determine the prevalence of hepatitis B and hepatitis C in the city of Buriticupu, MA, located in the Brazilian Eastern Amazon region, and try to explore the risk factors for these infections in that area. METHODS: Two hundred forty three subjects (46.5% male and 53.5% female) were investigated. RESULTS: The prevalence of past or current infection of hepatitis B and C virus was, respectively, 40.74% and 5.76%. Positivity for HBsAg was found in 2.88% of the subjects. The prevalence of current infection or chronic virus carriers found was 2.88% (HBsAg). There was a statistically significant relationship between the sera-prevalence of anti-HBc and the distance of the residence from the city center which may reflect an indirect association between the infection and precarious conditions of existence. Individuals with age equal or greater than 60 years were also more likely to be anti-HBc positive which could only reflect that older people have a longer history of exposure to hepatitis B infection. The prevalence of hepatitis C is higher than the worldwide estimate. CONCLUSION: Buriticupu may be considered endemic for hepatitis B and C. Hepatitis B infection could be related to precarious living conditions and old age. Hepatitis C was not associated with the variables investigated in the present investigation.